The Reformulation of Pancasila Constitutional State: Maqâshid al- Syarî`ah’s Perspective - Asmawi, Asmawi; Thamrin, Abu; Hidayatulloh, Hidayatulloh (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2022)
This study focuses on how maqâshid al-syarî`ah (sharia objectives) correlates with the reformulation of Pancasila constitutional state concept. Specifically, it aims at proving and explaining the relevance of maqâshid al-syarî`ah with the reformulation of Pancasila constitutional state concept. This study uses a qualitative research method that is based on theoretical-philosophical approach. Data were collected using documentary study techniques and were analyzed using qualitative content analysis techniques. The findings of this study indicate that the concept of Pancasila constitutional state has certain characteristics of constitutional state. The values and doctrines embedded in Pancasila are the state fundamental principles of Indonesia as well as the basic ideology of the state. In Islamic law perspective, the concept of Pancasila constitutional state has its substantial basis in maqâshid al-syarî`ah. This study proves that the concept of Pancasila constitutional state is theoretically valid and substantively connected to maqâshid al-syarî`ah, which includes justice (al-‘adl), affection (al-rahmah), public interest (al-mashlahah), wisdom (al-hikmah), and the five objectives (al- maqâshid al-khamsah). Penelitian ini berfokus pada bagaimanakah relevansi maqâshid al-syarî`ah dengan reformulasi konsep Negara Hukum Pancasila. Penelitian ini bertujuan membuktikan dan menjelaskan relevansi maqâshid al-syarî`ah dengan reformulasi konsep Negara Hukum Pancasila. Dalam penelitian ini diterapkan metode riset kualitatif berbasis pendekatan teoritis-filosofis, yang dalam pengumpulan datanya menggunakan tehnik studi dokumenter; dan data dianalisis dengan tehnik analisis isi secara kualitatif (qualitative content analysis). Temuan penelitian ini menunjukkan bahwa konsep Negara Hukum Pancasila memiliki ciri dan karakteristik Negara Hukum plus nilainilai dan kaidah-kaidah yang terkandung dalam Pancasila sebagai dasar negara dan ideologi bangsa Indonesia; dan dari perspektif hukum Islam, konsep Negara Hukum Pancasila punya basis substantif maqâshid al-syarî`ah. Penelitian ini menyimpulkan bahwa konsep Negara Hukum Pancasila terbukti valid dan otentik menurut sudut pandang teori maqâshid al-syarî`ah dan substansi maqâshid al-syarî`ah, yang meliputi al-‘adl, al-rahmah, al-mashlahah, al-hikmah, dan al- maqâshid al-khamsah.